Factors Affecting the Credit Risk Management in the Banking Sector of Pakistan: Moderating Effect of Financial Technology - Ghulam Murtaza; Muhammad Akbar Ali Ansari; Waseef ul Hassan; Muhammad Akhtar (International Journal of Business and Economic Affairs, 2023)
Credit Risk Management (CRM) identifies and manages the risks associated with lending and credit activities. This study investigates the impact of Environmental Risk (ER), Market Risk Analysis (MRA), Organizational Structure (OS), and Operational Efficiency (OE) on the Credit Risk Management (CRM) of the banking sector in Pakistan. Furthermore, examine the moderating effect of financial technology. The quantitative data was collected for this study by random sampling from different branches of banks in three cities of Pakistan. The Partial Least Squares (PLS) method is employed to analyze the data for this study. The study concludes that there is a significant role of Environmental Risk (ER), Market Risk Analysis (MRA), Organizational Structure (OS), and Operational Efficiency (OE) in credit risk management in the banking sector of Pakistan and a significant moderating role of financial technology. Furthermore, this study contributes a significant theoretical framework to the body of knowledge, enhancing the theory related to credit risk management. The practical implications of this study would streamline credit risk assessment processes and boost the efficiency of risk management, and credit decisions can now be made more quickly and reliably.